A Deliberation on Marketisation of Higher Education An Economic Critique on the Book The Marketisation of Higher Education and the Student as Consumer - Vahid Mehrbani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book titled The Marketisation of Higher Education and the Student as Consumer has acceptable diverse matters, but lacks a clear analytical method and inner coherence in content. An overview of book showed that three broad concepts as what, why and nature of higher education cover the main subjects of the book. Analysis of what is marketization reveals that in a marketized higher education system, the admission of students, the price charged, the regulations of admittance and so on are determined by demand and supply. Additionally, examining why is marketization suggests that economic pressures, the difficulty of governmental finance, an increase in social demands, globalization, and so forth are the most important factors of driving universities toward marketization. In addition, benefits such as improvement of efficiency and expansion of competition are the prime reasons justifying marketization. Finally, higher education is not a public good which government to be its organizer. Therefore, higher education has the intrinsic capability of performance in the market framework.